Recurrent glioblastoma: who receives tumor specific treatment and how often? - Steffens, Rieke; Semrau, Sabine; Lahmer, Godehard; Putz, Florian; Lettmaier, Sebastian; Eyüpoglu, Ilker Yasin; Buchfelder, Michael; Fietkau, Rainer (Journal of Neuro-Oncology, 2016)
The recurrence of glioblastoma (rGBM) is inevitable and often short-term. Therefore, information on the prognosis and effectiveness of tumor-specific versus purely palliative approaches should be more in-depth than a mere list of available treatment options for patients in this situation. However, follow-up data on the course of the disease in unselected patient populations after completion of primary treatment are scarce. This single-center analysis investigated the rate and number of glioblastoma recurrences after initial radiotherapy in 189 consecutive GM patients, focusing on the incidence of early death and the frequency of tumor-specific treatment (TST) versus best-supportive care (BSC) as well as the outcomes for the different approaches. In 61 % of initial population first recurrence (rGBM) could be determined by histology or imaging. 47 % received TST. 58 % of the patients with rGBM and TST were diagnosed with a second recurrence. Up to five recurrences were treated. 35-45 % of patients died before undergoing imaging studies to confirm the next recurrence. Multivariate analysis identified male sex and KPS score as independent factors (p < 0.01) for the choice of TST over BSC. Median overall survival from the diagnosis of first recurrence was 267 days in the TST group versus 65 days in patients receiving BSC (p < 0.0001). Nearly half of all rGBM patients received second-line TST, but a remarkably high proportion died early. Gender and KPS played a role in the choice of TST over BSC for recurrence treatment.
EVALuna2:18351